Sexo e sexualidade: a perspectiva do tema por professores da rede pública de educação - Santos, Viviane Gomes dos (Universidade Federal de São Carlos, 2024)
The history of Sexual Education in Brazil is marked by various forms of setbacks and censorship. Governed by religious and conservative morals, the country faces the subject with increasing aversion, resulting in deficient and challenging instruction. In this context, the present study aimed to understand how science and biology teachers perceive Sexual Education. A qualitative approach was used for this research, with semi-structured interviews as the main tool, conducted with teachers from the public school system in the city of São Carlos, São Paulo. The data obtained from the interviews were analyzed through Discursive Textual Analysis, from which three relevant dimensions emerged: Teachers’ Initial Training, The Importance Attributed to the Topic Within the Educational Context, and The Level of Knowledge on Gender and Sexuality. By discussing these factors, it was possible to reflect on how we can build the identity of the sexual educator, aspects of a healthy environment for discussion, the implementation of a curriculum more aligned with current debates, and the challenges faced in teaching the subject.
Sex and sexuality: the perspective of the topic by teachers in the public education system
Keywords: Educador sexual; Percepção docente; Gênero e sexualidade; Ensino democrático; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM